Tecnologia de medição não invasiva do encolhimento e homogeneidade de cores em processos têxteis - Dalton Cozac Tanos Jorge (2007)
This work presents three methodologies based on the digital acquisition and treatment of image for quality control in the textile industry, being two related to the dimensional control, and one related to the control of the fabric dye. The dimensional control is necessary during the sanforization, stage in which occurs the daily pay-shrinking of the fabric, to the step that the coloration control is necessary during the Coloration. The first methodology consists of counting the number of pixels between two made marks in the fabric before the sanforization and to compare with the number of pixels between the same marks after the process. Of this form the percentage of shrinking of the fabric can be calculated from the difference of the number of pixels between the markings in the two images. The second methodology uses the fast Fourier transformed (FFT) to analyze the images in the domain of the frequency. By the difference of the frequencies of the images before and after the process the percentage of shrinking of the fabric is determined. This same FFT also can be used to count the number of trams of the fabric in the image. The third methodology consists on the comparative analysis of the histograms of colors (RGB) of samples of one same neighborhood to verify the homogeneity of the coloration of the fabric. All the methods in subject presented quite satisfactory results, with high reliability metric, mainly if compared to the current techniques, also demonstrating a high use potential in the industry for its easy adaptation in lines of fabric finishing for monitor and control on-line of processes.